2011
DOI: 10.1002/masy.201150310
|View full text |Cite
|
Sign up to set email alerts
|

Spinnability of Nanofilled Polypropylene

Abstract: Summary: Spinnability of isotactic polypropylene iPP (melt flow 25 g/10 min) was studied after addition of three nanofillers at 0.3% by wt., two nanoclays and a modified hydrotalcite. TGA evidenced the increase of thermooxidation stability in nanofilled iPPs. All these iPP were successfully processed and tensile properties similar to those of iPP fibers were achieved. Processing and mechanical draw ratio were evaluated. Moreover, nanofilled iPP fibers appeared to be more prone to further drawing, as derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Stress at break values of the neat and nanofilled HDPE fibers were plotted versus draw ratio in Figure . Scientific literature showed various dependency of stress at break on nanofiller content, either increasing values after addition of 0.5–5 wt % of nanofiller, or unchanged, or even decreasing results, as in the case of nanofilled polypropylene fibers . In this case, stress at break for LDH‐1 and LDH‐2 remained practically unchanged in comparison with that of neat HDPE fibers (Figure ) up to DR15.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Stress at break values of the neat and nanofilled HDPE fibers were plotted versus draw ratio in Figure . Scientific literature showed various dependency of stress at break on nanofiller content, either increasing values after addition of 0.5–5 wt % of nanofiller, or unchanged, or even decreasing results, as in the case of nanofilled polypropylene fibers . In this case, stress at break for LDH‐1 and LDH‐2 remained practically unchanged in comparison with that of neat HDPE fibers (Figure ) up to DR15.…”
Section: Resultsmentioning
confidence: 87%
“…Recent literature evidences a lot of progress in the nanofilled bulk materials; on the contrary, there are relatively a few publications on fibers made of nanofilled polyolefins. For instance, PP fibers were produced with various types of nanofillers, for example, layered silicates, carbon nanotubes, and montmorillonite . In the case of HDPE, composites fibers containing calcium carbonate, carbon nanotubes, silica, and layered silicates were reported .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, starting from PP at relatively high melt flow (MF = 12 and 25 g/10 min) slightly lower T m values were already reported for both as-spun and drawn nanocomposite polyolefine fibers [18,21], and correspondently lower crystallinity content and T c values were observed. On the other hand, there are reports where growth of T m was indicated along with lower crystallinity [7,22]. Thus it can be concluded that higher crystallinity content and higher crystallization temperature in cooling reveal a possible nucleating role of FS.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 94%
“…The decrease in both tensile strength and strain at break at high nanofiller content, particularly in LDH-5 plates and LDH-3 fiber, has been attributed to the presence of hydrotalcite aggregates, that may behave as defects, and could also reduce the interfacial adhesion between the matrix and the filler [5,47]. Some other indications on the fiber drawing can be evaluated from the mechanical draw ratio " MEC , or the maximum drawability that is defined according to Equation (4): (4) where # b is the strain at break expressed in percentage [13,21]. At the same time, the maximum attainable strength $ MAX , is computable from the stress at break, $ b multiplied by the mechanical draw ratio, following Equation (5):…”
Section: Mechanical Properties Of Plates and Fibersmentioning
confidence: 99%
“…In particular, the organo-modified clay was considered responsible for the reduction of the fiber defects during drawing and for the higher attainable draw ratios [17]. On the other hand, various authors described the production of isotactic polypropylene fibers containing organo-modified clay with a double-step process consisting in a preliminary melt compounding with or without compatibilizer, followed by fiber spinning [19][20][21][22] or melt-spun bonding [23]. The fiber properties were found to be dependent on the polypropylene melt flow, ranging between 12 and 35 dg/min (230°C, 2.1 6kg), the nanoclay composition, and the spinning and drawing conditions.…”
Section: Introductionmentioning
confidence: 99%